Evaluation of vitamin D level in the blood serum of depressed women after childbirth in the city of Isfahan, Iran - Zahra Mohamaddokht; Akbar Karimi; Farahnaz Mardanian (Mashhad University of Medical Sciences, 2018)
Introduction: Postpartum depression is a serious temperamental and mental disorder. This condition seems to be affected by vitamins and minerals. Given the immediate effects of this disorder, the mother's inability to carry out maternal care, and the risks of suicide and infanticide and given that vitamin D receptors and hydroxylase enzymes are present in different regions of the brain, including amygdala this study was performed to determine the effect of vitamin D on postpartum depression treatment. Methods: This case-control study was carried out in 2014 in Shahid Beheshti Hospital of Isfahan, Iran, on women who had given birth 30 days earlier. Depression was assessed using the Edinburg Questionnaire. The data were analyzed in SPSS, version 20, using independent t-test (to investigate age variable), Mann-Whitney U test (to examine the frequency distribution of education level), Pearson correlation, and Chi-square test (to investigate the frequency distribution of the route of delivery). P-value less than 0.05 were considered significant. Results: The mean serum level of vitamin D showed a significant reduction in the case group as compared to that in the control group (P<0001). In other words, there was a significant relationship between the serum level of vitamin D and postpartum depression. Conclusion: As the findings indicated, postpartum depression was associated with the deficiency of vitamin D. regarding this; the use of vitamin D supplements during the prenatal period can be a proper way to prevent this disease.